The effects of acutely and subchronically applied DL-methionine on plasma oxidative stress markers and activity of acetylcholinesterase in rat cardiac tissue - Mićović, Žarko; Kostić, Sanja; Mutavdžin, Slavica; Andrejević, Aleksa; Stamenković, Aleksandra; Čolović, Mirjana; Krstić, Danijela; Djurić, Marko; Hrnčić, Dragan; Živković, Vladimir; Jakovljević, Vladimir; Djurić, Dragan (Vojnosanitetski pregled, 2021)
Background/Aim. Chronically induced hypermethioninemia leads to hyperhomocysteinemia which causes oxidative stress, atherogenesis, neurodegeneration and cancer. However, little is known about the acute and subchronic effects of DL-methionine (Met). The aim of study was to assess the effects of acutely and subchronically applied Met on oxidative stress parameters in rat plasma [enzymes: catalase (CAT), glutathione peroxidise (GPx), superoxide dismutase (SOD) and index of lipid peroxidation, malondialdehyde (MDA)], and acetylcholinesterase (AChE) activity in rat cardiac tissue. Methods. The enzymes activities, as well as MDA concentration were evaluated following acute (n = 8) and subchronic (n = 10) application of Met [i.p. 0.8 mmoL/kg body weight (b.w.) in a single dose in the acute overload or daily during three weeks in the subchronic overload]. The same was done in the control groups following application of physiological solution [i.p. 1 mL 0.9% NaCl (n = 8) in the acute overload and 0.1–0.2 mL 0.9% NaCl, daily during three weeks (n =10) in the subchronic overload]. Tested parameters were evaluated 60 minutes after application in acute experiments and after three weeks of treatment in subchronic experiments. Results. There were no difference in homocysteine values between the groups treated with Met for three weeks and the control group. Met administration significantly increased the activity of CAT and GPx after 1 h compared to the control group (p = 0.008 for both enzymes), whereas the activity of SOD and MDA concentrations were unchanged. Subchronically applied Met did not affect activity of antioxidant enzymes and MDA level. AChE activity did not show any change in rat cardiac tissue after 1 h, but it was significantly decreased after the subchronic treatment (p = 0.041). Conclusion. Results of present research indicate that Met differently affects estimated parameters during acute and subchronic application. In the acute treatment Met mobilizes the most part of antioxidant enzymes while during the subchronic treatment these changes seems to be lost. On the contrary, the acute Met overload was not sufficient to influence on the AChE activity, while longer duration of Met loading diminished function of the enzyme. These findings point out that methionine can interfere with antioxidant defense system and cholinergic control of the heart function.
Keywords: oxidative stress; methionine; homocysteine; rats; plasma; enzymes; cholinesterases